العوامل المنتجة للتجديد في أحكام التشريع الإسلامي: دراسة أصولية تحليلية - رائد نصري أبو مؤنس (International Institute of Islamic Thought, 2014)
يتناول هذا البحث تحديد العوامل المؤثرة والمنتجة لتجديد الأحكام في التشريع الإسلامي، وعملية الاجتهاد الموصلة إليه، وتمييزها عن العوامل غير المؤثرة، تمهيداً لضبط دعوى التجديد في التشريع الإسلامي. وتوصل الباحث إلى أن العوامل المتعلقة بالاجتهاد تتمثل في: إمكانية الخطأ عند المجتهد، واحتمالية تعدد الحق في القضية محل الحكم، أو اختلاف طرق الاجتهاد وترتيب الأدلة، أو تبدّل في الظن الغالب، ومدى الكفاءة العلمية التي أظهرها المجتهد في اجتهاده. أما العوامل المتعلقة بالحكم فهي: مدى قصد المشرع إعلامنا بالحكم أو عدمه، ومدى تغيُّر موضوع الحكم وتحوّله جوهرياً وشكلياً، التفرقة بين تغير وسائل الأحكام وتجددها، والأحكام ذاتها. وعليه فإن نسبة التغير للزمان والمكان نسبة غير حقيقية، وليس تبدل الزمان، أو اختلاف المكان سبباً لتجديد الحكم أو تغييره. This purpose of the paper is to identify factors that influence and produce new provisions in Islamic law, and the process of Ijtihad that yield Tajdid, and to distinguish these factors from non-influential factors in order to control the renewal claim in Islamic law. The researcher found that factors relating to ijtihad are: the possibility of error committed by the scholar, the possibility of having multiple rights on the issue, different ways of ijtihad arrangement of evidence, change in the prevalent conjecture, and the intellectual competence shown by the scholar. Factors related to the ruling are: the intent of the legislature to inform the ruling, the change in the subject of ruling in form and substance, the distinction between change and renewal provisions means, and the provisions themselves. Accordingly, the time and place are not the real factors in the production of tajdid and change in ruling.